Semi-automated approach in the evaluation of low bone mass using clavicle radiogrammetry technique - Snekhalatha, U; Ashok Kumar, D; javasan, Padma (International Journal of Engineering and Technology, 2018)
Background: Low bone mineral density increasing with age is a universally observed phenomenon. This leads to osteoporosis, which is a regressive change that occurs in the bone and it is diagnosed before the occurrence of fractures. The dual energy x -ray absorptiometry (DXA) is considered to be the standard measurement for the detection of bone mineral density (BMD).Objectives: To measure the various bone mass indices in the clavicle bone by radiogrammetric method from a posterior-to-anterior (PA) view of chest digital X-ray using semi- automated method.Methods: Forty women whose mean age was found to be 46.05Â±15.53 years were included in this study. For the total population (n=40), the right femur BMD was acquired by DXA scanner. The digital chest radiographs were taken for all the subjects. In all cases, the geometrical variables such as periosteal width (CLR-D), endosteal width (CLR-d), cortical thickness (CLR-CT) and percentage cortical thickness %(CLR-CT) were measured in the right clavicle bone region by semi-automated method approach developed in MATLAB software.Results: The CLR-CT (r=0.77) as well as with % CLR-CT (r=0.72) has provided statistically significant correlation (p < 0.01) with the total hip BMD in the total population studied. The pre-menopausal and post-menopausal of the studied population demonstrated a high significance value of (p < 0.01).Conclusion: The semi-automated measurement of low bone mass indices in clavicle radiogrammetry will be useful in the evaluation of low bone mass in post-menopausal women and elderly aged population. This method can be used as a screening tool for mass population, especially in rural India.